Musik sebagai Sarana Untuk Mengekspresikan Diri: Analisis Lirik Lagu “Membasuh” Karya Hindia - Arfian Suryasuciramdhan; Maulana Yusuf; Nessya Mayla Faiza; Rendi (Populer: Jurnal Penelitian Mahasiswa, 2024)
In this modern era, the continuous progression of music has had a critical effect on the rise of different sorts of songs. Music has become an integral part of society, serving as a loyal companion in various moments of life. The connection between humans and music has become undeniable. Music is not just a tool for entertainment, but also a powerful means of communication, allowing individuals to express themselves. From expressing feelings to conveying ideas and opinions, music serves as a vessel capable of depicting various aspects of human life. In this context, this research aims to analyze how the lyrics of the song "Membasuh" function as a medium of expression, by interpreting the lyrics and uncovering the hidden meanings within the song "Membasuh". The researcher employs a literature review research method. The findings of this analysis indicate that songs can be an effective medium for conveying self-expression, as reflected in the information available in online media related to the song "Membasuh", as well as from the songwriter who personally pours his life philosophy through the work to those around him.